2012
DOI: 10.1161/circheartfailure.111.965152
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Objectively Measured Medication Nonadherence in Adults With Heart Failure

Abstract: Background Medication nonadherence rates are high. The factors predicting nonadherence in heart failure (HF) remain unclear. Methods and Results A sample of 202 adults with HF was enrolled from the Northeastern U.S. and followed for 6 months. Specific aims were to describe the types of objectively measured medication nonadherence (e.g. taking, timing, dosing, drug holidays) and to identify contributors to nonadherence 6 months after enrollment. Latent growth mixture modeling (GMM) was used to identify distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 38 publications
3
82
3
1
Order By: Relevance
“…6,8,10,12,[21][22][23][24][25][26][27][28][29][30][31][32] Table 1 may assist the health care provider in recognizing predictors that may impact adherence to HF medications. Table 2 depicts a summary of the studies identifying predictors of decreased 6,8,10,[21][22][23][24][25][26]28,29,32 and increased 8,12,22,[26][27][28]30,31 HF medication adherence. Large, observational cohort studies extracting adherence and demographic data from health insurance claims databases or HF registries with 2 to 4 years of follow-up data from the United States found some similar significant predictors for nonadherence, including male gender or nonwhite race.…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…6,8,10,12,[21][22][23][24][25][26][27][28][29][30][31][32] Table 1 may assist the health care provider in recognizing predictors that may impact adherence to HF medications. Table 2 depicts a summary of the studies identifying predictors of decreased 6,8,10,[21][22][23][24][25][26]28,29,32 and increased 8,12,22,[26][27][28]30,31 HF medication adherence. Large, observational cohort studies extracting adherence and demographic data from health insurance claims databases or HF registries with 2 to 4 years of follow-up data from the United States found some similar significant predictors for nonadherence, including male gender or nonwhite race.…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 99%
“…Wu et al (2012) conducted a series of studies in HF patients to determine factors affecting event-free survival, factors defined as ED visits for symptoms of decompensated HF, HF or cardiac hospitalizations, and all-cause mortality. 31 The studies found that those who were not married (P = 0.044), 31 Lapses in attention 24 Excessive daytime sleepiness with or without mild cognitive decline 24,25 Advanced age (≥ 65 years) 29 …”
Section: ■■ Methods Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reported data on self-care in medication taking are high, education and support to appropriately use medication is still needed. In many populations older adults often use nonprescription and inappropriate drugs or forget to take their medication [26][27][28][29]. Patients may use herbal medication or traditional medication in addition to prescribed pharmacotherapy and may not be aware of drug interactions [30].…”
Section: Discussionmentioning
confidence: 99%
“…36 As the number of pills taken per day is increased, medication adherence increases. 41,42 Also, patients are more likely to skip a dose when they experience side effects. 41,42 Patient-related factors that affect medication adherence include forgetting, feeling that treatment has "succeeded" as evidenced by decreased or absent symptoms, excessive daytime sleepiness, poor attention span, and cognitive decline.…”
Section: Factors Of Medication Adherencementioning
confidence: 99%